Der musikalische Dillettant: eine Abhandlung des Generalbaßes - Daube, Johann Friedrich 1733-1797 (Vienna Kurzböck, 1771)
Daube was a German composer, music theorist and lutenist of the pre-classical period. He worked as a theorbist at the court of Frederick II in Berlin in his younger years, where he was also in constant contact with Carl Philipp Emanuel Bach. In 1744 he was appointed chamber theorist and flautist at the Stuttgart court orchestra. In 1770 he moved via Augsburg to Vienna, where he died in 1797. Daube described himself as a councillor and first secretary of the Imperial Franciscan Academy of Liberal Arts and Sciences. Daube's compositions show him to be a musician rooted in tradition, whose tonal language represents a link between the High Baroque, Empfindsamkeit and pre-classical periods.'Der Musikalische Dilettant: eine Abhandlung der Komposition,' a treatise on galant chamber music composition, is a unique and timely work that constitutes the keystone of Daube's theoretical writing. Yet its significance as an enlightening reflection of galant tastes and techniques has not been widely recognized, due perhaps to the attention given his treatise 'General-Baβ in drey Accorden' (1756), to confusion surrounding its identity as the second in a projected series of four Dilettant publications, and to the relative obscurity of its author in the history of music theory.Daube's awareness of the latest musical trends and his uniquely practical approach to composition in the current style stem from his experience as a performer on lute and flute in some of the foremost musical centers in the German-speaking lands – Berlin, Stuttgart-Ludwigsburg, Augsburg, and Vienna – where he worked among those who were influential in shaping musical styles and tastes.
2 parts in 1. The literature states that this work to have been published in 1773. However, the title page states 1771.
durch alle 24 Tonarten, mit untermengten Opernarien, ec. Solis, Duetten und Trio für die meisten Instrumenten
Keywords: 18th Century (1701-1800); Method; Basso continuo; Composing; Instrumental music; Vienna (Austria)